Analisis Pelayanan Perpustakaan Sekolah Terhadap Peningkatan Minat Baca Peserta Didik di MIN Gunung Maddah Sampang - Siti Farida; Nur Jamal (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2022)
In the current era of globalization, in the world of education there is competition between one institution and another. So the school library service here has a strong influence in increasing students' reading interest. Based on this, there are three research focuses that are the main studies in this study, namely: first, how is the school library service at MIN Gunung Maddah Sampang?, second, what is the strategy for school library services to increase student interest in reading at MIN Gunung Maddah Sampang ?, how is the evaluation of school library services to increase student interest in reading at MIN Gunung Maddah Sampang?. This research method uses a descriptive qualitative approach. The sources of data obtained are through interviews, observation and documentation. The informants are the principal, the head of the library, the manager of the service division, the Indonesian language teacher, the English teacher and also the students. The results showed that: first, the library of MIN Gunung Maddah Sampang has used automation or computerized services in terms of completing the administration of borrowing books, returning books and catalogs, which is an activity of providing library materials appropriately, accurately and quickly to meet the needs of users. This is in accordance with the library service system. Second, the school library of MIN Gunung Maddah Sampang also cooperates with regional libraries, in visiting smart homes and also mobile cars so that students can get to know a little about the services available in the library, in accordance with strategies in an effort to increase and foster reading interest in students. . Third, the MIN Gunung Maddah Sampang library involves principals and teachers in implementing strategies to increase students' reading interest through monthly programs and also activities such as reading corners, monthly literacy reading workshops, library exhibition activities and at the same time giving appreciation to students. So that all activities in the library can be maximized properly, according to the strategy in an effort to increase reading interest.